KINETIKA REAKSI FERMENTASI GLUKOSA HASIL HIDROLISIS PATI BIJI DURIAN MENJADI ETANOL - Salsabila, Usyqi; Mardiana, Diah; Indahyanti, Ellya (Jurusan Kimia, FMIPA Universitas Brawijaya, 2013)
Ethanol can be produced by glucose fermentation process using Saccharomyces cerevisiae. The potential source of glucose is starch of durian seed. This research studies about determine the kinetics model of ethanol fermentation of glucose and to identify the physical properties of ethanol produced. Glucose fermentation using Saccharomyces cerevisiae for 72 hours at various initial concentrations of 20, 40, 60 and 80 ppm has been conducted. After ethanol produced was reacted with potassium dichromate using Conway crucible. It was then analyzed by UV-Vis spectrophotometer at 605 nm. The physical properties of ethanol determined were density and refraction index. The result showed that the kinetics model of ethanol fermentation obtained was accordance with = -0,0011 + 0,0002 equation. As for Michaelis-Menten (Km) constant was 5,5 ppm-1 and maximum velocity (Vmax) 5000 ppm.hour-1. In addition, its physical properties i.e. density and refractive index were in the range of 0,9767-0,9809 g/mL and 1,3347-1,3365 respectively.